Otimização da produção de biossurfactantes por microrganismos isolados de painéis fotovoltaicos - Prado, Mateus Henrique Dezzotti (Universidade Federal de São Carlos, 2024)
Biosurfactants are amphiphilic molecules with great potential for application in the biotechnology industry, surpassing synthetic surfactants in terms of sustainability, degradability, reduced toxicity and resistance to different temperatures, pH and salinity. Microorganisms found in extreme anthropogenic environments have the potential to synthesize such molecules of biotechnological interest due to their ability to withstand extreme conditions. In this sense, the present study aimed to evaluate the production of biosurfactants by Serratia nematodiphila, Sphingomonas paucimobilis and Microbacterium hydrothermale isolated from photovoltaic panels. After confirmation of the synthesis by M. hydrothermale, production was optimized through a full factorial experiment, in which the chosen strain produced a molecule with low emulsifying capacity, but with surface tension reduction properties from 72 mN.m-1 to 34.20 mN.m-1 . Process monitoring included analyses of cell growth, sugar consumption, reduction of surface tension and pH, evidencing the production of the biosurfactant predominantly in the stationary growth phase and a productivity of 9.93 g.L-1 at the end of the 120 hours of fermentation. Additional tests demonstrated the emulsification capacity of the molecule with mineral oils ranging from 4.59% to 6.82%. Subsequently, physicochemical analyses indicated the production of an anionic biosurfactant of phospholipid nature with a critical micellar concentration of 3% (30 g.L-1 ), positive result for drop collapse, high capacity to provide greater surface wettability and oil spreading with a clear zone diameter of 4.7 cm. The stability of the molecule was determined within the temperature range of 20 to 70°C at neutral pH and NaCl concentration up to 10 g.L-1 . Further analysis confirmed the glycophospholipid nature of the produced biosurfactant with total sugar concentration of the molecule as 24.05%, while the total lipids estimate was 75.95%. Finally, the main functional groups –OH, C＝O, C＝C, –CH2 , C–O–C and aromatic rings present in the biosurfactant structure were determined from a semi-structural analysis in FTIR.
Optimization of biosurfactant production by isolated microorganisms of photovoltaic panels
Keywords: Biossurfactantes; Biosurfactant; Microbacterium Hydrothermale; Otimization; Otimização; CIENCIAS BIOLOGICAS::MICROBIOLOGIA